From generators to mirrors – a comparison of phonological theories - Krzysztof Jaskuła (Facta Simonidis)
This article offers a comparison of the main twentieth century phonological approaches to the idea of phonological goals and analytic methods. These formal approaches can be divided into the theories of rules (e.g. Generative Phonology) and the theories of representations (e.g. Government Phonology). What is shown below is the chief assumptions and goals of both theoretical frameworks as well as the formal mechanisms which help to achieve these goals. This is accompanied with examples of syllabic structures and analyses of phonological phenomena in both Polish and English.